Mechanical and morphological properties of different muscle-tendon units in the lower extremity and running mechanics: effect of aging and physical activity - Karamanidis, K.; Arampatzis, A. (The Journal of Experimental Biology, 2005)
The objectives of this work were (i) to investigate whether chronic endurance running is a sufficient stimulus to counteract the age-related changes in the mechanical and morphological properties of human triceps surae (TS) and quadriceps femoris (QF) muscle-tendon units (MTUs) by comparing runners and non-active subjects at different ages (young and old), (ii) to identify adaptational phenomena in running mechanics due to age-related changes in the mechanical and morphological properties of the TS and QF MTUs, and finally (iii) to examine whether chronic endurance-running exercise is associated with adaptational effects on running characteristics in old and young adults.